Artificial Intelligence In Education: Opportunities, Challenges, And Ethical Concerns - Chelghoum, Hanane; Chelghoum, Ahlem (The Journal of Studies in Language, Culture, and Society, 2025)
Artificial Intelligence (AI) is rapidly transforming education, offering innovative solutions that enhance learning, modernise administrative tasks, and provide personalised and engaging educational experiences. The present paper explores the integration of AI in education, analysing both its advantages and disadvantages. It also highlights AI-driven tools, such as intelligent tutoring systems, automated grading software, and virtual assistants, which are revolutionising teaching methodologies and making education more accessible and efficient. Beyond traditional classrooms, AI plays a crucial role in language learning, entrepreneurship, business education, research studies, and various other disciplines. However, its adoption presents significant challenges, including concerns over data privacy and the potential reduction of human interaction in learning environments. Besides, this paper reviews teachers’ and students’ perspectives on the role of AI in education, assessing its impact on engagement, critical thinking, and academic performance. Furthermore, ethical issues such as plagiarism, data security, and the need for regulatory policies are discussed to ensure effective and reliable AI implementation. Finally, as AI continues to evolve, its future in education depends on a balanced approach that maximises its potential while guaranteeing academic integrity and human involvement in learning.